2016
DOI: 10.1371/journal.pone.0158007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Maternal Nutrition on Oocyte Size and Quality, with Respect to Early Larval Development in The Coral-Eating Starfish, Acanthaster planci

Abstract: Variation in local environmental conditions can have pronounced effects on the population structure and dynamics of marine organisms. Previous studies on crown-of-thorns starfish, Acanthaster planci, have primarily focused on effects of water quality and nutrient availability on larval growth and survival, while the role of maternal nutrition on reproduction and larval development has been overlooked. To examine the effects of maternal nutrition on oocyte size and early larval development in A. planci, we pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 58 publications
3
50
1
Order By: Relevance
“…Moreover, CoTS can persist without food for many months (Moran 1986), and so it seems unlikely that it is a lack of coral per se, that causes elevated mortality or initiates mass exodus from reefs. It is possible, however, that limited access to preferred coral prey (e.g., Acropora) leads to compromised health and condition of CoTS (Lucas 1984;Caballes et al 2016), despite relatively high overall coral cover on reefs subject to moderate CoTS outbreaks.…”
Section: Question 9 (Adults) -What Causes the Rapid Disappearance Of mentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, CoTS can persist without food for many months (Moran 1986), and so it seems unlikely that it is a lack of coral per se, that causes elevated mortality or initiates mass exodus from reefs. It is possible, however, that limited access to preferred coral prey (e.g., Acropora) leads to compromised health and condition of CoTS (Lucas 1984;Caballes et al 2016), despite relatively high overall coral cover on reefs subject to moderate CoTS outbreaks.…”
Section: Question 9 (Adults) -What Causes the Rapid Disappearance Of mentioning
confidence: 99%
“…Caballes et al (2016) demonstrated that differences in the nutritional condition of female A. cf. solaris, based on contrasting diets (e.g., Acropora versus Porites), have a major bearing on the growth and performance of their progeny.…”
Section: Question 4 (Larvae and Juveniles) -How Important Is Diet In mentioning
confidence: 99%
See 3 more Smart Citations